THERMAL ANALYSIS OF A SMALL SCALE SOLID WASTE-FIRED STEAM BOILER FOR POWER GENERATION IN BENIN CITY, NIGERIA (Nigerian Journal of Technology, 2016)
Thermal analysis of a small scale solid waste-fired steam generator is presented in this paper. The analysis was based on the chosen design specifications which are operating steam pressure and temperature of 20bar and 400? respectively, solid waste consumption rate of 3.6ton/hr and a furnace utilizing grate-fired technology. The boiler is designed as a possible waste management option in Benin Metropolis and Nigeria at large with energy recovery. The average daily municipal solid waste (MSW) generation in Benin Metropolis was considered in order to assess the availability of the feed stock. A calorific value of 17.49MJ/kg was obtained for the solid waste using Dulong’s formula. Calculations based on energy balance in the boiler show that about 7.63kg/s of air is required to combust 1kg/s of MSW to produce about 3.437kg/s of steam. Further calculations show that about 1.4MW of electrical power can be obtained from the produced steam. http://dx.doi.org/10.4314/njt.v35i3.13